Industry as a Dominant in the Formation of an Ukraine’s Self-Sufficient Economy - Amosha, O.; Bryukhovetska, N.; Buleev, I. (Економічний вісник Донбасу, 2020)
For millennia, the traditional ancient, slave-owning, feudal economy was formed and developed at a slow pace, the basis of which was agricultural production, and handicraft (the predecessor of industry), services were insignificant in terms of their volumes, but their growth rates outstripped the growth rates of the agricultural sector, which reflects the Clarke model. In the industrial era, industry becomes the dominant sector of the economy, reaching a maximum in terms of its share in the economy of developed countries and the world by the middle of the 20th century as a result of predominantly extensive development, the I-II industrial revolutions, and the transformation of science into a direct productive force. In the II half of the twentieth century the development of industry goes on the path of intensive qualitative transformations (the third industrial revolution), and at the beginning of the twenty-first century developed countries entered the processes of the IV industrial (production) revolution, the development of scientific achievements, V, VI technological orders. The growth rates of the economy are accelerating, the share of industry in the economy is decreasing in relative terms, but in absolute terms, the growth of industry remains, despite the prevalence of the service sector in the modern economy (more than 60% in the world economy, more than 80% in the US economy). However, the basic industry, the dominant feature of the development of self-sufficient countries, remains industry, mechanical engineering, effectively mastering the scientific and technological achievements of IV IR, V, VI TO, ICT, digitalization. Research has proven the futility of the transition to a modern economy through the total destruction of industry, as is the case in post-socialist countries and in Ukraine. The expediency of restructuring the industry through the modernization of mechanical engineering is substantiated, which will ensure the restoration of the economy as a whole, its self-sufficiency, equal participation in the international division of labour and cooperation, entry and development as part of unions, associations of regional and international levels. Work on the development of the economy, the achievement of self-sufficiency of the state and society should be accompanied by an increase in the spirituality of a person as a spiritual-bio-social subject, collectives, civil society and its institutions. Тисячоліттями повільними темпами формувалася і розвивалася традиційна антична, рабовласницька, феодальна економіка, основу якої складало сільськогосподарське виробництво, а ремісництво (попередник промисловості), послуги за своїми обсягами були незначними, але темпи їх зростання випереджали темпи зростання аграрного сектору, що відображає модель секторів економіки Кларка. В індустріальну епоху домінуючим сектором економіки стає промисловість, досягаючи максимуму за питомою вагою в економіці розвинених країн і світу до середини ХХ ст. в результаті переважно екстенсивного розвитку, І-ІІ промислових революцій, перетворення науки в безпосередню продуктивну силу. У ІІ половині ХХ ст. розвиток промисловості переходить на шлях інтенсивних якісних перетворень (ІІІ промислова революція), а на початку ХХІ ст. розвинені країни увійшли в процеси IV промислової (виробничої) революції, освоєння досягнень науки, V, VI технологічних укладів. Темпи зростання економіки прискорюються, питома вага промисловості в економіці знижується у відносних характеристиках, але в абсолютних показниках зберігається зростання промисловості, незважаючи на переважання у сучасній економіці сфери послуг (понад 60% у світовій економіці, понад 80% в економіці США). Однак базовою галуззю, домінантою розвитку самодостатніх країн, залишається промисловість, машинобудування, які ефективно освоюють науково-технологічні досягнен¬ня IV ПР, V, VI ТУ, ІКТ, цифровізацію. Дослідженнями доведено безперспективність переходу до сучасної економіки шляхом тотального руйнування індустрії, як це відбувається в постсоціалістичних країнах та Україні. Обґрунтовується доцільність шляхом модернізації машинобудування реструктурувати промисловість, що забезпечить відновлення економіки в цілому, її самодостатність, рівноправну участь у міжнародному поділі праці і кооперації, входження і розвиток у складі спілок, асоціацій регіонального та міжнародного рівнів. Робота з розвитку економіки, досягнення самодостатності держави та суспільства має супроводжуватися зростанням духовності людини як духовно-біо-соціального суб'єкта, колективів, громадянського суспільства та його інститутів. Тысячелетиями медленными темпами формировалась и развивалась традиционная античная, рабовладельческая, феодальная экономика, основу которой составляло сельскохозяйственное производство, а ремесленничество (предшественник промышленности), услуги по своим объёмам были незначительными, но темпы их роста опережали темпы роста аграрного сектора, что отражает модель секторов экономики Кларка. В индустриальную эпоху доминирующим сектором экономики становится промышленность, достигая максимума по удельному весу в экономике развитых стран и мира к середине ХХ в. в результате преимущественно экстенсивного развития, І-ІІ промышленных революций, превращения науки в непосредственную производительную силу. Во ІІ половине ХХ в. развитие промышленности переходит на путь интенсивных качественных преобразований (ІІІ промышленная революция), а в начале ХХІ в. развитые страны вошли в процессы IV промышленной (производственной) революции, освоение достижений науки, V, VI технологических укладов. Темпы роста экономики ускоряются, удельный вес промышленности в экономике снижается в относительных характеристиках, но в абсолютных показателях сохраняется рост промышленности, несмотря на преобладание в современной экономике сферы услуг (более 60% в мировой экономике, более 80% в экономике США). Однако базовой отраслью, доминантой развития самодостаточных стран остаётся промышленность, машиностроение, эффективно осваивающие научно-технологические достижения IV ПР, V, VI ТУ, ИКТ, цифровизацию. Исследованиями доказана бесперспективность перехода к современной экономике путём тотального разрушения индустрии, как это происходит в постсоциалистических странах и в Украине. Обосновывается целесообразность путём модернизации машиностроения реструктуризировать промышленность, что обеспечит восстановление экономики в целом, её самодостаточность, равноправное участие в международном разделении труда и кооперации, вхождение и развитие в составе союзов, ассоциаций регионального и международного уровня. Работа по развитию экономики, достижению самодостаточности государства и общества должна сопровождаться ростом духовности человека как духовно-био-социального субъекта, коллективов, гражданского общества и его институтов.